PatchMatch Filter‐Census: A slanted‐plane stereo matching method for slope modelling application. Issue 3 (9th July 2021) - Eng, Weiyong; Koo, Voonchet; Lim, Tiensze
Abstract: Image matching is a well‐studied problem in computer vision. Conventional image matching is solved using image feature matching algorithms, and later deep learning techniques are also applied to tackle the problem. Here, a slope‐modelling framework is proposed by adopting the image matching techniques. First, image pairs of a slope scene are captured and camera calibration as well as image rectification are performed. Then, PatchMatch Filter (PMF‐S) and PWC‐Net techniques are adapted to solve the matching of image pairs. In the proposed PatchMatch Filter‐Census (PMF‐Census), slanted‐plane modelling, image census transform and gradient difference are employed in matching cost formulation. Later, nine matching points are manually selected from an image pair. Matching point pairs are further used in fitting a transformation matrix to relate the matching between the image pair. Then, the transformation matrix is applied to obtain a ground truth matching image for algorithm evaluation. The challenges in this matching problem are that the slope is of a homogenous region and it has a slanted‐surface geometric structure. In this work, it is found out that the error rate of the proposed PMF‐Census is significantly lower as compared with the PWC‐Net method and is more suitable in this slope‐modelling task. In addition, to show the robustness of the proposed PMF‐Census against the original PMF‐S, further experiments on some image pairs from Middlebury Stereo 2006 dataset are conducted. It is demonstrated that the error percentage by the proposed PMF‐Census is reduced significantly especially in the low‐texture and photometric distorted region, in comparison to the original PMF‐S algorithm. This further verifies the suitability of the PMF‐Census in modelling the outdoor low‐texture slope scene.